ANALISIS DAN PERANCANGAN JARINGAN KOMPUTER UNTUK IMPLEMENTASI SISTEM INFORMASI PADA WINDOWS SERVER 2016 MENGGUNAKAN INTERNET DAN INTRANET DI UNIVERSITAS TEKNOLOGI SUMBAWA - Rodianto; Ahmad Juliansyah (Jurnal Informatika Teknologi dan Sains, 2019)
Internet and intranet network is a facility used to support the educational process, especially the process of learning. Sumbawa University of Technology (UTS) is one of the private universities in Sumbawa, West Nusa Tenggara Province. The server is a device owned by the campus data center to support the performance of the academic community in the implementation of information systems. In addition, the UTS is currently still reviewing the development of wired and wireless networks to support the implementation of the procurement system with other information technology equipment. This study aimed to analyze and design computer networks for the implementation of the system on windows server 2016 using the internet and intranet Case Studies University of Technology Sumbawa. The method used for the development of a network that is Prepare, Plan, Design, Implement, Operate, Optimize (PPDIOO). Successful testing implementation conducted through Implement information systems. Instrument data collection techniques in this study using literature study, observation, and interviews. The end result of this research is on the server computer information systems can be run via the internet and intranet useful to support the performance of the academic community of the university.